FOOD DYES (E-171, E-173) AND CHANGES CAUSED BY THEIR USE - Oltiboyeva Mavsuma G’ulom qizi (Web of Journals Publishing, 2024)
Food additives or food dyes (E-171, E-173) are substances added for technological purposes to give the necessary properties and qualities to products during production, packaging, transportation or storage. They are used as certain dyes, flavors, preservatives (Alyakhnovich, NS, 2015; Alyakhnovich NS, Novikov DK, 2016). These dyes are used in the cosmetics industry, in the production of cigarettes, oil, flour, toothpaste, confectionery, chewing gum, candy, fast food, beverages, cheese and many other products, as well as in the pharmaceutical industry. According to the chemical composition, these food additives are E-171 titanium dioxide, E-173 aluminum. E-171 titanium dioxide - formula TiO2.
Keywords: E-171, E-173, preservative, xenobiotic, cytotoxic.